The Engineering journal. - Engineering Institute of Canada (Montreal Engineering Institute of Canada)
Includes the annual reports of the Institute's Council, committees and branches, issued 1919-56 in a regular no. and 1957- as a supplement to the Apr. no.
Beginning with August 1918 the Engineering index, prepared by the staff of the American Society of Mechanical Engineers, is published each month in the issues of the journal.
Keywords: Engineering -- Periodicals; Engineering -- Societies, etc; Engineering -- Indexes